2020
DOI: 10.1515/pac-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)-catalyzed amination in the synthesis of chiral derivatives of BINAM and their evaluation as fluorescent enantioselective detectors

Abstract: A mini-review covers recent successes in the synthesis of (S)-1,1′-binaphthyl-2,2′-diamine (BINAM) using Pd(0)-catalyzed amination reactions. As a result, versatile compounds with C2-chiral backbone were synthesized, among them are derivatives bearing additional chiral amino and fluorophore groups like dansyl amide, 7-methoxycoumarin, 6-aminoquinoline, different macrocyclic compounds with oxadiamine and polyamine linkers were obtained as well. BINAM derivatives of various structures were evaluated as fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…BINAM has long been considered by researchers as a potential fluorescent detector for the efficient chiral recognition of αphenylethylamine and tryptophan enantiomers. [28] Previous studies have shown that probes based on BINAM can highly selectively recognize lysine in aqueous solutions, but the results indicated a significant fluorescent response for both configurations, thus unable to distinguish the configuration of lysine. [29] This article reports the discovery and synthesis of an innovative fluorescent probe, which demonstrates exceptional selectivity for L-lysine under physiological conditions.…”
Section: Introductionmentioning
confidence: 95%
“…BINAM has long been considered by researchers as a potential fluorescent detector for the efficient chiral recognition of αphenylethylamine and tryptophan enantiomers. [28] Previous studies have shown that probes based on BINAM can highly selectively recognize lysine in aqueous solutions, but the results indicated a significant fluorescent response for both configurations, thus unable to distinguish the configuration of lysine. [29] This article reports the discovery and synthesis of an innovative fluorescent probe, which demonstrates exceptional selectivity for L-lysine under physiological conditions.…”
Section: Introductionmentioning
confidence: 95%
“…BINAM has long been considered by researchers as a potential fluorescent detector for the efficient chiral recognition of α-phenylethylamine and tryptophan enantiomers. [25] Previous studies have shown that probes based on BINAM can highly selectively recognize lysine in aqueous solutions, but the results indicated a significant fluorescent response for both configurations, thus unable to distinguish the configuration of lysine. [26] This article has discovered and synthesized a fluorescent probe that can selectively recognize L-lysine with high selectivity in physiological conditions.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, the carbon-platinum [32] and fluorine-doped tin oxide(FTO) [33] electrodes gave 2a in 43% and 29% yields, respectively, with low current efficiencies (entries 2 and 3). Other alcoholic reaction solvents, such as methanol, ethanol, and trifluoroethanol, reduced the yield of 2a to 6-12% with current efficiencies of 4-8% (entries 4-6), along with a 5% yield of aza [5] helicene. HFIP, an appropriate solvent for the reaction, serves as an excellent hydrogen bond donor and provides highly persistent radical cations [34,35].…”
Section: Optimization Of the Reaction Conditionsmentioning
confidence: 99%
“…1,1 -Bi-2-naphthylamine (BINAM) and its derivatives are widely used as building blocks for transition-metal ligands and organocatalysts [1][2][3][4], as well as chiroptical materials for fluorescence sensing [5][6][7]. Among their syntheses, transition-metal mediated coupling of 2-naphthylamine derivatives has been well established [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%